Reef fish monitoring as a coral reef resilience indicator in the Sempu Strait, South of East Java, Indonesia - GATUT BINTORO; ANDIK ISDIANTO; NUDDIN HARAHAB; ANDI KURNIAWAN; AGUS DWI WICAKSONO; RELIA MAHARDITHA; AULIA LANUDIA FATHAH; BERLANIA MAHARDIKA PUTRI; MUCHAMAD FAIRUZ HAYKAL; MUHAMMAD ARIF ASADI; ARIEF SETYANTO; TRI DJOKO LELONO; OKTIYAS MUZAKY LUTHFI; DWI CANDRA PRATIWI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bintoro G, Isdianto A, Harahab N, Kurniawan A, Wicaksono AD, Maharditha R, Fathah AL, Putri BM, Haykal MF, Asadi MA, Setyanto A, Lelono TD, Luthfi OM, Pratiwi DC. 2023. Reef fish monitoring as a coral reef resilience indicator in the Sempu Strait, South of East Java, Indonesia. Biodiversitas 24: 4950-4959. Sempu Island is designated as a nature reserve which is surrounded by a fairly high diversity of coral reefs. Since the high activities of fishing ports near this island, the anthropogenic pressure seriously became a threat to the biodiversity of coral reefs in this nature reserve. Continuous observation of reef fish is an important activity to monitor the coral reef health condition. Since then, bimonthly monitoring using an underwater visual census has been conducted from October 2021 to May 2022. Based on these observations obtained that the average reef fish abundance was in the "low" category, namely 0.516 ind/m2 in October 2021, 0.527 ind/m2 in December 2021, 0.522 ind/m2 in February 2022, and 0.378 ind/m2 in May 2022. The abundance of reef fish obtained consisted of three categories: indicators, targets, and majors. Overall, the Pomacantridae family, from the major fish category, has the largest abundance compared to other families. While the range of coral coverage was 6-21.3%, which was included in the "bad" category. There was a relationship with a value of 0.462 (medium) between coral cover and fish abundance. The abundance of reef fish at 21.4% was influenced by coral cover, while the remaining 78.6% was influenced by other factors outside of the tested variables. The decline in reef fish abundance in 2015-2022 can be caused by a decrease in coral cover in the Sempu Strait.